2009
DOI: 10.1152/ajpendo.90796.2008
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of receptors for orexigenic factors in nodose ganglion of diet-induced obese rats

Abstract: The vagal afferent pathway is important in short-term regulation of food intake, and decreased activation of this neural pathway with long-term ingestion of a high-fat diet may contribute to hyperphagic weight gain. We tested the hypothesis that expression of genes encoding receptors for orexigenic factors in vagal afferent neurons are increased by long-term ingestion of a high-fat diet, thus supporting orexigenic signals from the gut. Obesity-prone (DIO-P) rats fed a high-fat diet showed increased body weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 26 publications
(34 reference statements)
7
73
1
1
Order By: Relevance
“…A previous study in our laboratory found no significant difference in the gene expression of the leptin receptor (Ob1R) between LF, DR, or DIO rats (32). Therefore, decreased Ob1R levels are unlikely to explain the reduction in leptin signaling in the VAN of DIO rats.…”
Section: Discussionmentioning
confidence: 78%
“…A previous study in our laboratory found no significant difference in the gene expression of the leptin receptor (Ob1R) between LF, DR, or DIO rats (32). Therefore, decreased Ob1R levels are unlikely to explain the reduction in leptin signaling in the VAN of DIO rats.…”
Section: Discussionmentioning
confidence: 78%
“…Direct morphological evidence identified that GHS-R1a was produced in the stomach-projected afferent neurons of the nodose ganglion in rats, suggesting that ghrelin signals from the stomach are transmitted to the brain via vagal afferent nerves (Sakata et al, 2003). Obesity-prone rats fed a high-fat diet had increased body weight, increased adiposity, and increased mRNA expression of GHS-R1a and CB 1 -R in the nodose ganglion compared with low-fat diet-fed control rats or high-fat diet-induced obesity-resistant rats (Paulino et al, 2009), demonstrating that shifts in the balance between orexigenic and anorexigenic signals within the vagal afferent pathway might influence food intake and body weight gain induced by high-fat diet.…”
Section: Normal Physiology Expression and Regulation Of Growth Hmentioning
confidence: 98%
“…They may also act in the periphery to indirectly alter food intake, insulin secretion, gastric emptying, fuel utilization, and energy expenditure (14,203,249,255). Less is known about vagal afferent signals and a large number of other humoral factors known to regulate appetite and energy balance (88,178), as they have yet to be studied in the obese after weight loss or during weight regain (Fig. 3, A and B).…”
Section: The Gut: Sensing the Prandial Statementioning
confidence: 99%